2018
DOI: 10.1002/jcp.26374
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical unloading reduces microtubule actin crosslinking factor 1 expression to inhibit β‐catenin signaling and osteoblast proliferation

Abstract: Mechanical unloading was considered a major threat to bone homeostasis, and has been shown to decrease osteoblast proliferation although the underlying mechanism is unclear. Microtubule actin crosslinking factor 1 (MACF1) is a cytoskeletal protein that regulates cellular processes and Wnt/β-catenin pathway, an essential signaling pathway for osteoblasts. However, the relationship between MACF1 expression and mechanical unloading, and the function and the associated mechanisms of MACF1 in regulating osteoblast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 52 publications
1
38
0
Order By: Relevance
“…MACF1 overexpressed preosteoblast was constructed as described previously (Yin et al, 2018). Briefly, MC3T3-E1 cells (1×10 7 per well) were electroplated (1800V and 30 ms) with the MACF1 overexpression plasmid pEGFP-C1A-ACF7 or control plasmid pEGFP-C1A using Neon Transfection System (Invitrogen) following the manufacturer's instructions.…”
Section: Establishment Of Macf1 Knockdown and Overexpressed Cell Modelsmentioning
confidence: 99%
“…MACF1 overexpressed preosteoblast was constructed as described previously (Yin et al, 2018). Briefly, MC3T3-E1 cells (1×10 7 per well) were electroplated (1800V and 30 ms) with the MACF1 overexpression plasmid pEGFP-C1A-ACF7 or control plasmid pEGFP-C1A using Neon Transfection System (Invitrogen) following the manufacturer's instructions.…”
Section: Establishment Of Macf1 Knockdown and Overexpressed Cell Modelsmentioning
confidence: 99%
“…In previous studies, Macf1 has been found to participate in the regulation of osteoblast differentiation‐associated Wnt/β‐catenin signalling pathway . In our previous studies, it was demonstrated that Macf1 can regulate the proliferation, cell cycle progression and differentiation of MC3T3‐E1 osteoblastic cell line . However, it remains unknown whether Macf1 could regulate bone formation in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In osteoblasts, mechanical stimulation causes a rapid, transient accumulation of active β-catenin in the cytoplasm and its translocation into the nucleus [34]. Furthermore, we reported that β-catenin reduction caused by simulated microgravity (Figure 5b) [14] and overexpression of β-catenin partially attenuated the negative effects of simulated microgravity on osteoblast differentiation ( Figure 6). Thus, we wonder whether β-catenin acts as a mechano-mediator in the processing of r-irisin, by regulating osteoblast differentiation under simulated microgravity.…”
Section: Discussionmentioning
confidence: 85%
“…According to reports, there are many osteoporosis risk factors such as cytokines (e.g., interleukin) [11,12], hormones (e.g., parathyroid hormone) [13], and signaling pathways molecules (e.g., wingless-type MMTV integration site family (Wnt), bone morphogenetic protein(BMP)) [14,15], regulating bone metabolism under microgravity environment. Skeletal muscles and bone, as neighboring tissues, are the two largest tissues in the musculoskeletal system [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation